Efektivitas Penggunaan Ekstrak Daun Pepaya (Carica papaya L.) SebagaiPengendalian InfestasiArgulus sp. Pada Ikan Koi (Cyprinus carpio) - Khoiriah Harahap; Suri Purnama Febri; Siti Komariyah; Iwan Hasri (Jurnal Airaha, 2021)
The purpose of this study was to analyze the effectiveness of papaya leaf extract (Carica papaya L.) as a control for Argulus sp. on koi fish (Cyprinus carpio) and analyzed the appropriate concentration of papaya leaf extract (Carica papaya L.) for the release of Argulus sp. on the body of koi fish (Cyprinus carpio). The method used is an experimental laboratory with a completely randomized design (CRD). The treatments were P1 (8 ml), P2 (10 ml), P3 (12 ml), P4 (14 ml) with three replications. The results of the ANOVA test showed that the immersion of papaya leaf extract had a significant (P>0.05) effect on the release time of Argulus sp., Argulus sp.death time, Argulus sp.'s mortality, while it had no significant effect (P<0.05) on survival rate ( SR). The best papaya leaf extract for controlling Argulus sp. in koi fish, namely in treatment P4 (14 ml) with an average time of death 8 minutes 90seconds.